Mikrobiálna dekontaminácia koreňových kanálikov devitálnych zubov - Kováč, Ján; Kováč, Daniel (Epidemiologie, mikrobiologie, imunologie, 2012)
The primary goal of endodontic therapy is the reduction or elimination of microorganisms and their by-products from the root canal system. Although a number of instrumentation and irrigation techniques exist, debris is often left behind in the root canal system and proper canal cleaning, shaping, and irrigation are needed to reduce significantly or sometimes even eliminate microorganisms from the canals. Residual microbes in the root canal system are the primary cause of post-treatment apical periodontitis that may persist in both poorly and properly treated cases. Apical periodontitis is a sequel to endodontic infection and manifests itself as the host defense response to microbial challenge emanating from the root canal system to the periapical tissue. It results in local inflammation, resorption of hard tissues, destruction of other periapical tissues, and eventual formation of various histopathological categories of apical periodontitis, commonly referred to as periapical lesions. When the root canal treatment is carried out properly, healing of the periapical lesion usually follows, with bone regeneration. In certain cases, post-treatment apical periodontitis still persists, the condition being commonly referred to as endodontic failure. It is widely acknowledged that such post-treatment apical periodontitis occurs when root canal treatment has not adequately controlled and eliminated the infection. However, complete elimination of microorganisms is not always achieved in clinical practice due to the anatomical complexities of root canals and consequent limitations in access by instruments and irrigants. The use of antimicrobial medication has been advocated to disinfect the root canal system. The recovery of Candida albicans and Enterococcus faecalis is common after failed root canal treatment. Therefore, when testing different antimicrobial agents for efficacy in endodontic treatment, 100% inhibition of the growth of the two microorganisms is required. The purpose of this article is to assess the antimicrobial action of intracanal medicaments and relevance of the root canal irrigation in endodontic therapy of devitalized teeth.
Keywords: zuby neživé; Anti-Infective Agents; periapikální periodontitida; Root Canal Irrigants; prostředky na výplach kořenových kanálků; lidé; antiinfekční látky; Tooth, Nonvital; Humans; Periapical Periodontitis